A contundência das soluções estruturais nos concursos nacionais de anteprojetos de arquitetura: 1958-1969 - Alvaro Pompeiano de Magalhaes Drummond (2006)
The present work tries to understand the relations between supporting structures and architectural form within a group of draft-projects presented and rewarded in contests between 1958 and 1969, in Brazil. The study is based on a descriptive theoretical and comparative approach and its general objective consists in identifying the several ways of using and conceiving the structure and its relation with the whole architectural object and project through the analyzed examples. It also searched relations between themes of these contests and the architectural solutions offered and between the technique employed and the period examined